Microalgae biotechnology and its role in sustainable and healthy food design - Schneider, Adriane Terezinha; Machado, Richard Luan Silva; Dutra, Darissa Alves; Machado, Eduarda Funari; Dias, Rosangela Rodrigues; Deprá, Mariany Costa; Zepka, Leila Queiroz; Jacob-Lopes, Eduardo (Frontiers in Bioengineering and Biotechnology, 2025)
Current food systems face a paradox: although scientific and technological advances have increased production capacity, they still cannot ensure nutritious and sustainable diets for everyone worldwide. In this context, microalgae stand out as promising bioresources due to their nutritional value, functional properties, and environmental benefits. This review critically examines the current state of microalgae biotechnology for food applications, focusing on cultivation methods, processes, techno-functional properties, regulatory challenges, and consumer perceptions. The analysis indicates that, despite notable progress in cultivation systems and approaches to integration and intensification, high production costs and inconsistent methods of characterizing microalgal biomass remain major obstacles to limit large-scale competitiveness. Additionally, legislation and consumer acceptance issues create a gap between laboratory innovations and industrial implementation. To make microalgae a mainstream ingredient, it is essential: (i) align safety standards and regulations; (ii) incorporate economic feasibility and sustainability; and (iii) develop strategic approaches that translate scientific advancements into practical consumer benefits. Therefore, this study, which explores the intersection of biotechnology, nutrition, and economics, offers a valuable framework to help turn microalgae from a promising idea into a practical solution within global food systems.